(untitled) (PANGEEA, 2025)
A feasibility study is based on a detailed topographic survey that describes very well the configuration of the terrain on the altitude, but also the possibility to determine any object in Stereographic 1970 coordinates necessary for detailed studies. The method of carrying out topographic surveys can be based on classic or modern technologies, which ensure uniformity, precision and a large number of points per surface unit. Combined technology was chosen, photogrammetric flight with high-resolution camera, but also LiDAR data. By combining these two technologies, the best results can be obtained. Of course, field measurements are also needed to determine control points (Ground Control Points - GCP) or landmark. Checkpoints for the accuracy of the orthophotoplane and the MDT and MDS were also determined. Special point cloud processing programs were used.